2014
DOI: 10.1038/leu.2014.209
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and epigenomic co-evolution in follicular lymphomas

Abstract: Follicular lymphoma (FL) with a t(14;18) is a B-cell neoplasm clinically characterized by multiple recurrencies. In order to investigate the clonal evolution of this lymphoma, we studied paired primary and relapse tumor samples from 33 patients with recurrent non-transformed t(14;18)-positive FL. We reconstructed phylogenetic trees of the evolution by taking advantage of the activation-induced cytidine deaminase (AID)-mediated somatic hypermutation (SHM) active in the germinal center reaction using sequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 37 publications
7
38
1
1
Order By: Relevance
“…Conventional cytogenetics was available in 3 cases; 2 of them (PTFL25, PTFL36) presented a normal karyotype 46,XY in all cells studied whereas case PTFL24 displayed a 47,XY,add(7)(q36),18 [15]/ 46,XY [5] altered karyotype (supplemental Figure 1A).…”
Section: Igh/igk Clonality Fish and Cytogenetic Analysis In Ptflmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional cytogenetics was available in 3 cases; 2 of them (PTFL25, PTFL36) presented a normal karyotype 46,XY in all cells studied whereas case PTFL24 displayed a 47,XY,add(7)(q36),18 [15]/ 46,XY [5] altered karyotype (supplemental Figure 1A).…”
Section: Igh/igk Clonality Fish and Cytogenetic Analysis In Ptflmentioning
confidence: 99%
“…10,11 In past years, the genetic landscape of conventional FL, beyond the well-known BCL2 translocation, 12 has been characterized comprehensively using next-generation sequencing (NGS). [13][14][15][16][17][18] This and similar high-throughput approaches revealed that germinal center (GC)-derived lymphomas are characterized by frequent mutations of histonemodifying genes. In adult-type FL, histone methyltransferase KMT2D (formerly MLL2) and EZH2, and the histone acetylases CREBBP, EP300, and MEF2B, are the most commonly mutated genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, whereas FL cells carry evidence of intraclonal evolution related to the ongoing somatic hypermutation process, mutational analysis of immunoglobulin variable regions reveals a counterselection of mutations affecting BCR structural integrity. 3,4 Finally, resistance to anti-idiotype therapy was shown to rely on mutations of the targeted immunoglobulin sequence rather than on loss of BCR expression. 5,6 Study of the FL BCR signaling profile highlighted a lack of constitutive activation together with a strong interindividual variability in both magnitude and kinetic of the signal.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, hypermethylation of tumor suppressor genes has been demonstrated in numerous studies including FL [56,57], with a significant overlap noted between hypermethylated CpGs and PRC2 target genes in embryonic stem cells [58]. Although initial reports suggested conservation of methylation profiles between paired pre-and post-transformation samples [58], the introduction of higher resolution platforms, suggests measurable differences in relapsed and more aggressive tumors [59,60]. Recent studies by Clozel et al propose a paradigm shifting change in how epigenetic therapies may be used to greatest effect; in a study of DLBCL, low-dose DNMTi exposure was used as a means of sensitizing chemoresistant tumors to doxorubicin through increased expression of a restricted number of genes including SMAD1 and demonstrated that combination of pretreatment with 5-azacitidine followed by chemoimmunotherapy recapitulated this observation in a Phase I clinical trial [61].…”
Section: Dna Methylationmentioning
confidence: 99%